Spatial and temporal changes of breast-conserving surgery rates and its influential factors among Chinese patients with breast cancer from 2013 to 2019: a registry-based study - Pengpeng Ye; Yuan Yang; Wei Hu; Lingyan Dai; Erwei Song; Shunrong Li; Liling Zhu; Kai Chen; Yanjie Xu; Xiaoyu Wang; Jianli Zhao; Jianrong He; et al. (BMJ Open)
Objective Our study aims to evaluate the spatial and temporal changes of breast-conserving surgery (BCS) rates and influential factors of BCS in Guangdong Province, China.Design, setting and participants This registry-based cohort study analysed the data of patients of all age groups, from the medical record cover page, which was mandatorily collected for inpatients by the Health Administrative Department of Guangdong Province, China. Patients with non-metastatic breast cancer, who underwent breast surgery between 2013 and 2019, were included.Main outcomes and measures We analysed the BCS rate in Guangdong Province between 2013 and 2019. Logistic regression was applied to investigate the association between patient-level influential factors and BCS, respectively. We used restricted cubic spline regression to model the non-linear association between hospital volume rank with BCS rate. Linear regression was used to evaluate the association between city-level parameters with BCS rate of each city.Results A total of 93 521 patients with non-metastatic breast cancer, who underwent breast surgery, were included in the analyses. Among them, 10 949 (11.7%) had BCS, with the BCS rates increasing from 0.8% in 2013 to 19.2% in 2019. Patients who were older (vs <40 years, 40–49 years: adjusted OR 0.72, 95% CI 0.68 to 0.76; 50–59 years: 0.51, 95% CI 0.48 to 0.54; ≥60 years: 0.37, 95% CI 0.35 to 0.40) and married (vs unmarried, 0.64, 95% CI 0.59 to 0.70) were less likely to undergo BCS. Patients who were employed (vs unemployed, 1.58, 95% CI 1.49 to 1.68), received cross-city surgery (vs local surgery, 1.37, 95% CI 1.31 to 1.44), lived in a high-income city (vs low-income city, β=4.40, 95% CI 1.55 to 7.24) or in a city with a higher number of physicians per 100 000 residents (0.57, 95% CI 0.31 to 0.82) were more likely to receive BCS.Conclusions and relevance This study suggests a significant increase in BCS rates from 2013 to 2019 in Guangdong, China. Promotion of BCS is needed, particularly among older patients, lower-volume hospitals and economically underdeveloped areas. Healthcare system should be prepared to support the increased awareness of seeking BCS among younger patients with breast cancer by improving the availability of radiotherapy, multidisciplinary team and patients’ education programme.